Resurrecting “Das Jesus Video”: translating a bestselling science fiction novel from German into English - Endres, John (My University, 2020)
This dissertation explores the process of translating the best-selling German science fiction novel, “Das Jesus Video” (1998) by Andreas Eschbach, into English. The novel was written in German and had previously been translated into a range of other languages, but not into English. The aim of the research was to create a part-translation of the novel to establish which translating strategies could be used to produce a commercially viable translation; to provide a review of the process of translating the novel; and to obtain information from the author on the reasons why this novel was not translated, even though some other novels by the same author have been translated into English. The theoretical framework is based on poly system theory and a longitudinal review of German science fiction and its relationship to science fiction in English. The study reveals that the reasons why the novel was not translated into English are external rather than related to the text itself: in the original German, the novel is written in a very accessible style that adopts features of English-language bestsellers and which poses few challenges to the translator. However, the receptiveness of the English-language literature market to literature originally written in other languages is relatively low for reasons related to the commercial and cultural dominance of the English language
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Arts in Translation by Research, 2020